Effects of the ABCB1 c.3435C>T (rs1045642) Polymorphism on Heat Pain Perception in Opioid-Free Adults With Chronic Pain. (21st July 2021) - Hooten, W. Michael; Hu, Danqing; Cunningham, Julie M.
Abstract : BACKGROUND: The adenosine triphosphate-binding cassette, subfamily B, member 1 gene ( ABCB1 ) encodes P-glycoprotein (P-gp) that influences the intracellular transport of solutes including endogenous opioid peptides. The primary objective of this study was to determine the effects of the ABCB1 polymorphism c.3435C>T (rs10454642) on heat pain (HP) perception in a group of opioid-free adults with chronic pain. METHODS: Opioid-free adults with chronic pain consecutively admitted to a pain rehabilitation program comprised the study cohort (N = 134). Individuals were genotyped for the c.3435C>T (rs10454642) polymorphism. The polymorphism was analyzed with nonparametric tests using a dominant (cytosine-cytosine [CC] versus cytosine-thymine [CT] + thymine-thymine [TT]) and recessive (CC + CT versus TT) model of allele effects. Quantitative sensory testing was performed using the Computer Aided Sensory Evaluator IV system. RESULTS: The distribution of genotypes was 22% (N = 29) for CC, 45% (N = 60) for CT, and 33% (N = 45) for TT (Hardy-Weinberg, P > .1). A significant association was observed between the recessive model and HP threshold. Standardized values of HP threshold were significantly greater in the TT group than the CC + CT group (median difference, −0.77; 95% confidence interval [CI], −1.49 to −0.23; P = .005), and the effect size estimate was small (Cliff delta = 0.30). In the dominant model, no significant difference in HP threshold was observed between the CC and CT + TT groups (median difference, −0.45; 95% CI, −1.15 to 0.00; P = .108). CONCLUSIONS: These results posit that the efflux of endogenous opioid peptides is reduced in individuals with the TT genotype due to lower expression of P-gp, which, in turn, results in higher HP threshold. This study contributes to the emerging understanding of how the ABCB1 c.3435C>T polymorphism contributes to pain perception in opioid-free adults with chronic pain and provides the foundation for investigating the potential effects of this polymorphism on the clinical course of chronic pain.